Using the Experiences and Perceptions of Health Care Workers to Improve the Health Care Response to the COVID-19 Pandemic. (November 2022) - Trinh, Lieu Thi Thuy; Stubbs, Joanne M.; Gilroy, Nicole; Schindeler, Suzanne; Achat, Helen
Background: We sought the opinions of health care workers (HCWs) at a designated COVID-19 facility receiving the first cases to identify workplace modifications and inform effective changes to maximize health and safety at the onset of a crisis. Methods: A cross-sectional study utilized open- and close-ended questions gathered demographic and work details, experiences and perspectives on infection control, communication, support, and the workplace. Qualitative data were analyzed thematically and quantitative were analyzed using descriptive statistics. Findings: Of 340 HCWs, most approved of the organization's response to minimizing risk (81.0%), infection control training (81.1%), and supplies (74.3%). Key actions included up-to-date guidelines (93.6%) and specialized infectious diseases clinics (94.9%). Conclusions: HCWs rated the organization's adaptive changes highly, noting areas for improvement such as transparency and timeliness of communication. Incorporating input from HCWs when responding to health crises was beneficial to maximize staff health and safety and consequently that of patients.